2014
DOI: 10.1089/cap.2013.0103
|View full text |Cite
|
Sign up to set email alerts
|

Guanfacine Extended Release Adjunctive to a Psychostimulant in the Treatment of Comorbid Oppositional Symptoms in Children and Adolescents with Attention-Deficit/Hyperactivity Disorder

Abstract: Objective: The purpose of this study was to assess the effect of guanfacine extended release (GXR) adjunctive to a psychostimulant on oppositional symptoms in children and adolescents with attention-deficit/hyperactivity disorder (ADHD). Methods: A multicenter, double-blind, placebo-controlled dose-optimization study of GXR (1-4 mg/d) or placebo administered morning (a.m.) or evening (p.m.) adjunctive to psychostimulant was conducted in subjects ages 6-17 with suboptimal response to psychostimulant alone. Subo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
0
20
0
2
Order By: Relevance
“…As in ADHD, high levels of hyperactivity and impulsiveness can contribute to oppositional behavior in children with ASD. In a placebo-controlled trial of 461 children aged 6-17-year-old with ADHD, the use of GEXR as an adjunct to stimulant treatment resulted in significantly greater improvement in oppositional behavior, as measured by the oppositional subscale of the Conners' Parent Rating Scale-Revised: Long Form (CPRS-R:L), compared with stimulant treatment alone [14]. Compared to placebo, atomoxetine also showed significant improvement in oppositional behavior, as measured by the HSQ, in a sample of children with ASD and moderate or greater ADHD symptoms [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in ADHD, high levels of hyperactivity and impulsiveness can contribute to oppositional behavior in children with ASD. In a placebo-controlled trial of 461 children aged 6-17-year-old with ADHD, the use of GEXR as an adjunct to stimulant treatment resulted in significantly greater improvement in oppositional behavior, as measured by the oppositional subscale of the Conners' Parent Rating Scale-Revised: Long Form (CPRS-R:L), compared with stimulant treatment alone [14]. Compared to placebo, atomoxetine also showed significant improvement in oppositional behavior, as measured by the HSQ, in a sample of children with ASD and moderate or greater ADHD symptoms [5].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these results suggest that GEXR may be an alternative to methylphenidate for monotherapy in children with ASD complicated by hyperactivity and oppositional behavior, particularly for those who do not show a positive response or cannot tolerate methylphenidate. It may also be useful in combined treatment with methylphenidate [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results verify the feasibility and acceptability of treating ADHD by stimulating α 2A -adrenoceptors in the PFC or up-regulating the NE concentration in synapses and extrasynaptic space in the PFC. Actually, the α 2A -adrenergic agonists guanfacine and clonidine have been used experimentally and clinically to treat ADHD [92][93][94][95][96][97] . The selective inhibitor of the NE transporter atomoxetine (tomoxetine or LY139603) has also been reported to alleviate ADHD symptoms [98] .…”
Section: N Ew Insights To Develop a Primate Model Of Adhdmentioning
confidence: 99%
“…60 Finally, patients receiving GXR plus psychostimulant demonstrated significant reductions on the oppositional subscale of the CPRS-R:LF compared to those taking placebo plus psychostimulant, both in the overall study population, as well as in the subgroup of subjects with significant baseline oppositional symptoms. 61 Cost-effectiveness of guanfacine for ADHD ADHD is a costly disease associated with a large economic burden to society and the health care system. 62,63 However, a growing body of research has shown that pharmacotherapy is cost-effective compared with no treatment or behavioral therapy alone among children and adolescents with ADHD.…”
Section: 55mentioning
confidence: 99%